PTH-087 Fam5C, a Possible Causal Molecule in Ulcerative Colitis Revealed through a Transcriptomic Analysis of the Bowel Mucosa - Smith, P J; Levine, A P; Sewell, G W; O’Shea, N R; Rodriguez-Justo, M; Novelli, M R; Vega, R; Bloom, S L; Smith, A M; Segal, A W (Gut, 2013)
IntroductionAbnormalities of the colonic mucosa have been implicated in the pathogenesis of ulcerative colitis (UC). We investigated mRNA profiles of macroscopically non-inflamed mucosal biopsies from the colon in patients with UC, Crohn’s disease (CD) and control subjects without gastrointestinal disease (HC), to identify genes that might be involved in the aetiology of the disease. Methods Paired biopsies were taken for histology and mRNA extraction from macroscopically non-inflamed mucosa in the ascending and descending colon, and the rectum, from 24 patients with UC, 14 with CD and 27 HCs undergoing routine colonoscopy. Patients were in complete clinical remission and were either on no treatment or on 5-aminosalicylates ± azathioprine. cRNA was hybridised to Illumina HumanHT-12 v4 Expression Beadchips. Array expression data were log transformed and normalised. Only probes with a detection p-value < 0.01 were analysed. Differential gene expression analysis between groups (using p < 0.05 FDR correction) and outlier analysis (p < 0.005, fold change (FC) ≥1.5) were performed at each location using customised software. Results were verified by qPCR and candidate molecules were examined in an independent cohort of UC patients. Results In group comparisons, of the 26,261 expressed probes, Family with Sequence Similarity 5, member C (FAM5C) was the only gene to be significantly under-expressed in UC, both in the rectum (FC = –1.58, p = 0.0008) and the descending colon (FC = –1.64, p = 0.0011). Outlier analysis showed that FAM5C was also grossly under-expressed in the ascending colon in 37.5% of UC patients, demonstrating that its expression is abnormal throughout the colon in a significant proportion of individuals. Expression levels were not abnormal in CD. Expression of FAM5C in UC did not correlate with the known markers of inflammation, IL-8, S100A8, DEFA5 and DEFA6, or with treatment. The under-expression of FAM5C in UC was confirmed in biopsies of non-inflamed rectal mucosa from an independent cohort of patients (FC = –1.68, p = 0.0073) and by qPCR (p < 0.001). Conclusion This is the first description of the under-expression of FAM5C in UC. As these observations were made in non-inflamed mucosa, low levels of this protein might be involved in the pathogenesis of the disease. Indications that FAM5C may function as tumour suppressor [1], could link to the observed predisposition to colonic malignancy in UC. Disclosure of InterestNone Declared. Reference Kuriowa T et al. (2009) Oncol Rep, 1005–11.